His Dark Materials : Once Upon a Time in the North - Book .5 - Pullman, Philip, 1946-; Lawrence, John, 1933- (New York : A Yearling book, 2008)
American balloonist Lee Scoresby and armored bear Iorek Byrnison meet when Lee and his hare daemon crash-land their trading balloon onto a port in the far Arctic North and find themselves in the middle of a political powder keg.
"A companion to His dark materials"--Cover.
Keywords: Balloonists -- Juvenile fiction; Arctic regions -- Juvenile fiction; Fantasy